Examining the corporate competitive capabilities of Malaysian manufacturing SMEs - Zulkiffli, Siti Nur ‘Atikah; Perera, Nelson (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2012)
The purpose of this paper is to examine the relationship between corporate competitive capabilities, which consists of cost leadership, differentiation, innovative marketing and customer service; and business performance.The paper is a quantitative-based approach using data obtained from the manufacturing sector of small to medium enterprises in Malaysia. Empirical results from structural equation modeling (SEM) demonstrate that corporate competitive capabilities had significant influence on its business performance. The paper has limitations due to a small response rate, would show short of a firmer conclusion from the analysis.This paper will contribute to the literature on strategic management, SMEs and resource-based view theory.This study isparticularly new in the context of the Malaysian SMEs manufacturing industry.The findings provide useful guidance to Malaysian SMES’ practitioners and policy-makers, by understanding the unique capabilities of their firms.